PENGARUH SALES GROWTH, CAPITAL INTENSITY DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023) - Azahra, Nabila Firza; Yazid, Abu (Jurnal Nusa Akuntansi, 2025)
This research aims to analyze the influence of Sales Growth, Capital Intensity, and Company Sze on Tax Avoidance in non-cyclicals consumer industry companies listed on the Indonesia Stock Exchange for the period 2019-2023. The type of research used is quantitative research with secondary data sources. By using a purposive sampling method based on predetermined criteria. The results of this research show that Sales Growth, Capital Intensity, and Company Size simultaneously influence Tax Avoidance. The Sales Growth variable shows that it partially has no effect on Tax Avoidance. The Capital Intensity variable partially shows an effect on Tax Avoidance. The Company Size variable partially shows an effect on Tax Avoidance.